The effect of sulphate-sulphide mineral baths on blood glucose level in patients with knee osteoarthritis - Erceg-Rukavina, Tatjana; Dragičević-Cvjetković, Dragana; Djuric, Dragan M; Stojiljković, Miloš P; Škrbič, Ranko (Scripta Medica, 2022)
Background/Aim: Type 2 diabetes is a common comorbidity in patients with knee osteoarthritis. Bearing in mind that obesity and insulin resistance are risk factors for the development of knee osteoarthritis, physical therapy and balneotherapy containing hydrogen sulphide (H2S) has a positive effect on the functional and metabolic status of these patients. This work was aimed to investigate the effect of sulphate-sulphide-rich mineral baths containing H2S on the level of serum glucose in patients with knee osteoarthritis.Methods: An open prospective randomised clinical trial included patients suffering from stage I and II of the knee osteoarthritis. Patients were divided into two groups of 40 subjects each: control group and experimental group. All subjects underwent inpatient physical treatment consisting of kinesitherapy and transcutaneous electrical nerve stimulation (TENS) 6 days a week. Patients from experimental group, in addition to all the mentioned treatments, also took sulphate-sulphide mineral water baths once a day for 30 minutes for 7 days, unlike the patients from control group who took tap water baths, according to the same schedule. The level of serum glucose was monitored in all patients on admission, after discharge and 6 months after the treatment. The Student t-test was used for statistical data processing, and p ˂ 0.05 was considered as statistically significant. Results: Study included 80 patients of both sexes, with an average age of 67.00 ± 5.75 years. All patients had elevated serum glucose values on admission. The initial levels of glycaemia in the control and experimental groups were not significantly different (6.99 ± 1.95 and 7.88 ± 1.90 mmol/L, respectively). At discharge, patients who performed balneotherapy had a statistically significant decrease in serum glucose values compared to patients from the control group (by 1.84 vs 0.26 mmol/L, p ˂ 0.001). This effect did not persist six months after the end of the treatment (p > 0.05).Conclusion: The application of balneotherapy with sulphate-sulphide mineral baths containing H2S as a potent gas transmitter significantly reduces serum glucose levels in patients with knee osteoarthritis.
Keywords: Hydrogen sulphide; Balneology; Osteoarthritis; Knee